PENGEMBANGAN RPP IPS MATERI PEMANFAATAN SUMBER DAYA ALAM TUMBUHAN BAGI MASYARAKAT PADA SISWA KELAS IV SD - Zildjianshi, Dhini Afrilia (LPPM STKIP PGRI Bandar Lampung, 2020)
This research aims to develop the Implementation Plan of Social Science Learning in Elementary School on the material Utilization of Plant Natural Resources for the Community. The method used in this research is Research and Development (R&D), produces new products and then tests the effectiveness of the product. The result of this research is to develop the utilization of plant natural resources for the community and conduct community-oriented assessments. That way the process of implementing learning can run well.